2013
DOI: 10.1177/1029864913486793
|View full text |Cite
|
Sign up to set email alerts
|

Music on the timing grid: The influence of microtiming on the perceived groove quality of a simple drum pattern performance

Abstract: In general, microtiming is considered to be an important factor for the perceived quality of rhythms. Our experiment analyzed the influence of early or late time shift of both bass drum and snare drum on the perceived musical quality of a short, simple drum pattern in rock style. In a web-based study, music students (N = 93) listened to a simple drum pattern played on a snare and a bass drum and evaluated the musical quality (in terms of the "groove quality") of five degrees of microtiming deviations (early an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
96
5
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(112 citation statements)
references
References 37 publications
10
96
5
1
Order By: Relevance
“…Earlier theoretical considerations emphasized the roles of subtle timing deviations (microtiming; participatory discrepancies) between players/instruments (Keil & Feld, 1994;Iyer, 2002;Pressing, 2002), but recent studies failed to find a positive correlation between microtiming and perceived groove (Madison et al, 2011;Davies et al, 2013;Frühauf et al, 2013). In fact, as timing deviations increase, perceived groove decreases, particularly among musically trained individuals (Davies et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Earlier theoretical considerations emphasized the roles of subtle timing deviations (microtiming; participatory discrepancies) between players/instruments (Keil & Feld, 1994;Iyer, 2002;Pressing, 2002), but recent studies failed to find a positive correlation between microtiming and perceived groove (Madison et al, 2011;Davies et al, 2013;Frühauf et al, 2013). In fact, as timing deviations increase, perceived groove decreases, particularly among musically trained individuals (Davies et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…In many styles associated with groove (e.g., jazz, R&B), rhythms are swung to varying degrees and, thus, systematically deviate from deadpan timing. Other studies have found that microtiming deviations were not required to give a sense of groove (Butterfield 2010, Fruhauf et al 2013, Madison 2006, Senn et al 2016, and in some cases, deadpan timings were preferred. These results make some sense, as Repp (2005) has noted that the phase corrections one makes in following fine-grained timing variations are often subliminal and involuntary, whereas only larger shifts in tempo (i.e., period corrections) involve conscious awareness and volitional control.…”
Section: Groovy Structural Factors: Swing and Syncopationmentioning
confidence: 99%
“…Perhaps surprisingly, only a few experiments have shown that microtiming is positively related to the experience of groove (Klichenmann and Senn ). Most studies have shown the opposite – that the more microtemporally extreme the rhythm, the less listeners experience the desire to move (See Madison and Sioris ; Butterfield ; Davies, Madison, Silva and Gouyon ; and Frühauf, Kopiez and Platz ) . Psychological experiments have found another rhythmic feature that more reliably relates to the pleasurable desire to move in groove: syncopation .…”
Section: Syncopation Entrainment and Affectmentioning
confidence: 99%